Experimental Study Of Installation Of Non Centric Light Steel C Profile On Light Steel Beam Frame - Ardani, Anggun Febri; Sulistiyorini, Dewi; Shulhan, M Afif (Journal of Green Science and Technology, 2019)
Light steel is one of materials that support the growth of construction technology at this time and it is generally used on roof truss contruction. The profile of light steel is a kind of steel profile which has dimension of thickness that is relatively thin with ratio of wide dimension of each profile element towards its huge thickness. In the assembling and installation, roof truss of light steel which is often encountered, cross section of C profile is connected by attaching body parts of two profiles or connecting wing parts with giving the connecting canal.This research uses the experimental method by flexural test with two points loading. The light steel which is used in this reserach is light steel of C profile by Ton Dong brand. The size is 75 x 35 x 0,75 mm andthe dimensions of beam frame specimenis 180 cm lengthand 25 cm hight, as many as 3 specimens with non centric profile overview. The research result shows that the average value of flexural strength is5,25 kNand the average of tensile strenght is 2281,67 N, while the result of experimental test uses UTM (Universal Testing Machine), the maximum strength is 5,92 kN and deflection 38,95 mm. The result of SAP 2000 analysis, the maximum deflection is 2,04 mm and 6 kN load.?Keywords : Light steel of C profile, Light steel beam frame, Test of flexural stength.